3G handset and network design - Varrall, Geoffrey (Wiley, 2003)
Written for hardware and software engineers, this hands-on guide shows you how to integrate handheld devices and cell phones with wireless network hardware and software. Geoff Varrall and Roger Belcher arm you with an in-depth understanding of the nuts and bolts of cellular handset and network hardware and software design, how handset hardware and software is evolving, and the role the technology plays in shaping offered traffic and building traffic value.